Сектор за управување со проекти во современото бизнис работење: предизвици, можности и препораки - Калешовска, Неда (Економски факултет, УКИМ, Скопје, 2020)
The universal uncertainty as well as the continuous competitive pressure, are leading an increasing number of organizations to implement and apply project management nowdays. This situation, without a doubt, leads to an increased pressure in managing projects, both from the premise of successful project management, but also from the premise of realization of the right projects, that brings us to the concept of Project Management Office (PMO). To these regards the goal of this doctoral diseration is to present both the teorethical and the practical aspects of Project Management Office (PMO) in contemporary business environment. This doctoral diseration gives a sinthesized analysis of the concept of PMO in one research summary, opening, analyzing and discovering the numerous and important questions and dilemmas surrounding this concept. Furthremore, this paper analyzes the challenges and opportunities of this organizational entity as well as the recommendations for the same. Special focus in this doctoral dissertation is put upon the analysis of the status of project management and PMO in the Republic of North Macedonia. The research analysis conducted within this thesis, gives conclusions about the status and movements of the trends both in respect to project management and in respect to PMO on industry level, on organization size level, as well as on overall level for the Republic of North Macedonia. Furthermore, this thesis conducts comparative analysis between Macedonia and the worldwide trends, in order that it generates an all-inclusive overview with conclusions and recommendations for the PMOs in Republic of North Macedonia, but in the same time, knowing the universality of the topic, on a more general level as well. What this doctoral dissertation offers is knowledge, answers, analysis, synthesis, experience and recommendations for a successful setup and management of the organizational unit, PMO, as a response for the ever increasing needs, dynamics, changes and evolution that are imposed today, more than ever, leading to successful projects and positive opportunities for continuous realization and growth.
Project management office in contemporary business environment: challenges, opportunities and recommendations
Докторска дисертација одбранета во 2020 година на Економскиот факултет во Скопје, под менторство на проф. д–р Лидија Пулевска Ивановска.
Keywords: project management; portfolio management; project management office; contemporary business environment